An Ethical Evaluation of Thomas Hobbes’ Political Authority - Foysal (The Jahangirnagar Review, 2024)
There is no country or society in the world where political authority does not exist, individuals or groups have either accepted the legitimacy of the political authority that grants this power for the sake of necessity or are often forced to abide by it. The important question is, can ‘necessity’ morally justify the exercise of power over us? One of the questions discussed in political philosophy and ethics is, should we accept political authority where there are sometimes undesirable conditions for us? Thomas Hobbes (1588-1679) in his book Leviathan, stated that human nature is selfish and human life would be lonely, poor, inferior, wild, and short-lived if there is no controlling disciplinary legislative authority which is a need for us and also morally valid. This paper will figure out some limitations of these views of Hobbes in the light of eclectic theories and practical aspects, including Jean-Jacques Rousseau, and John Locke in the first strand. Immanuel Kant and J. S. Mill’s views have been used to ethically evaluate Hobbes’ position of political authority in the later strand.